Novel approach for high (secure and rate) data hidden within triplex space for executable file - Zaidan, A.A.; Zaidan, B.B.; Alanazi, Owaid Hamdan; Gani, Abdullah; Zakaria, Omar; Alam, Gazi Mahabubul (Academic Journals, 2010)
Steganography is an art that involves the concealing of information with the aim of making the communication invisible. Unlike cryptography, where the main aim is to secure communications from the Snooper by encoding that data in such a way that it becomes visible but not understood. In this paper, we propose a framework that will integrate both steganographic and cryptographic approaches within a hyiperd space of an EXE file. This approach will be used for highly securing data that is hidden; using both the advance encryption standard (AES) method and statistical technique (ST) computation. To further address the security issues, we will use the EXE as a cover for the hidden data; the executable file cover was selected in this approach because of its ability to hide huge amounts of data within a hyiperd space of an EXE file which in turn overcomes the problem of the data hiding quantity. The use of the EXE file also makes sure that the changes made to it will not be detected by anti-virus and its functionality will not be negatively affected after the hiding process, features of the short-term responses were simulated, and indicated that the size of the hidden data does depend on the size of the Unused Area1+ Unused Area 2 + Image Pages; within the cover file which is equal to 28 of the size of the exe.file before the hiding process. Most antivirus systems do not allow direct writing into executable files, so the approach of the proposed system is to prevent the hidden information from being disclosed by these systems and the exe.file still functioning normally after the data hiding process.